Pengaruh Tunjangan Kinerja, Komitmen Tugas dan Loyalitas Kerja Terhadap Kinerja Pegawai Pada Kantor Camat Batam Kota - Rabiah, Rabiah; Laili, Saripah; Junaidi, Junaidi; Sulaksono, Wedly; Sumardin, Sumardin (eScience Humanity Journal, 2024)
This study was conducted with the aim to determine the effect of performance allowance, task commitment and job loyalty on employee performance at the Batam City Sub-District Office. The population in this study were employees of the Batam City Sub-District Office with a total population of 41 employees. Determination of the number of samples using saturated sample technique, so that the number of samples was 41 employees. The sampling technique is probability sampling. Data collection was carried out by distributing questionnaires to respondents. The data that has been collected is processed using SPSS data processing software. From the results of the study it is known that performance allowances have a significant effect on employee performance, task commitment has a significant effect on employee performance and loyalty has no significant effect on employee performance. Simultaneously performance allowances, task commitment and work loyalty have a significant effect on employee performance. The adjusted R square value is 0.683 or 68.3%. This means that performance allowances, task commitment and work loyalty are able to explain employee performance by 68.3%, while the remaining 31.7% is influenced by other factors not included in this research model.